Programa “Mundo Rojo” como estrategia educativa para mejorar el autoestima en estudiantes de tercer grado de Educación Primaria-Trujillo, 2021 - Aguilar Luján, Daimler Georg (2022)
The objective of this research was to determine the effect of the "Red World" Program as an educational strategy to improve self-esteem in third grade students of primary education of the Educational Institution No. 81017 "Santa Edelmira"-Trujillo, 2021. The research design it was pre-experimental with pre and post-test; the sample population consisted of 34 students, to whom the Program was applied, which consisted of 14 clown workshops. The instrument used to measure self-esteem was the Coopersmith Self-Esteem Inventory (SEI), school version. The results obtained indicate that all students stood out in 14.71% at the high average level and 85.29% of students at the high self-esteem level, this determined that the Wilcoxon statistical test indicates a value of p = 0.000 < 0.05. Therefore, it is concluded that the workshops of the Program have considerably improved self-esteem in students.